ETNOMOTANI OBAT TRADISIONAL OLEH MASYARAKAT KUTAI DI KEC. MUARA BENGKAL KAB. KUTAI TIMUR - Hadijah, Siti; Hendra, Medi; Hariani, Nova (Jurusan Biologi, Fakultas Matematika dan Ilmu Pengetahuan Alam, 2016)
This studied aim to find out the traditional medicinal plants that used by communities at Kutai area in the subdistrict of Muara Bengkal, how the Kutai community obtains a medicinal plants and which part of the plant that used as a traditional medicine. In this studied we used PRA (Participatory Rural Appraisal) methods, interview open-ended technique and the informant was determined by using snowball sampling. Stages of research include survey, observation, interviews, sampling, doing the identification of the herbarium and data analysis using Microsoft Excel 2007. There are 82 species of medicinal plants that are grouped into 42 families was found in this research. The Kutai community gained the medicinal plant by planted on their home garden, took on the field, looking for in the forest and bought in the market. The plant parts that used as a traditional medicine are the leaf, rhizome, stem, fruit, root, bark, seeds, tree sap, bulbs and the entire section.